LIQUID-LIQUID EXTRACTION OF IRON (III) FROM OUENZA IRON ORE LEACH LIQUOR BY TRIBUTYLPHOSPHATE - Nouioua, A.; Barkat, D. (University of Eloued جامعة الوادي, 2017)
The solvent extraction of iron (III) from the hydrochloric acid leach liquor of iron ore from mine of Ouenza, Algeria with tributylphosphate (TBP) in chloroform was studied. The effect of several parameters, such as contact time, HCl concentration, TBP concentration and chloride inorganic salt (KCl) concentration on the efficiency of extraction of iron was examined at 19Â±2 Â°C. It was found that, for 2 min 3M TBP in presence of 5M HCl and 2 M of KCl can cause high extraction (98.57 %) of iron (III). The stoichiometry of the extracted species was determined by using the method of slope analysis. The number of moles of H+, Â and TBP associated with the extracted species was determined and the extracted species was found to be HFeCl4(TBP)2.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: solvent extraction; iron (III); Tributylphosphate; leach liquor; Mine Ouenza.